(untitled) (Journal of the College of Education for Women, 2018)
In the present paper, the researcher attempts to shed some light on the objective behind inserting some Qur’anic verses by Al-Zahraa (Peace Be Upon Her) in her revered speech. Besides, it tries to investigate the hidden meaning of these verses and to study them in the light of pragmaticreferences. This task is supported by Books of Tafseer as well as the books that explained this speech to arrive at its intended meaning. It is possible say that this is astep towards studying speeches of ’Ahlul Bayt’ (People of the Prophet’s household) in terms of modern linguistic studies, as well as employing modern methods to explore the aesthetic values of these texts.